A retrospective study of tracheal collapse in small-breed dogs: 110 cases (2022–2024) - Kim, Mi-Rae; Kim, Se-Hoon; Ryu, Min-Ok; Youn, Hwa-Young; Choi, Ji-Hye; Seo, Kyoung-Won (Frontiers in Veterinary Science, 2024)
The grade of tracheal collapse (TC) is assessed by the diameter of the narrowed lumen. However, studies on the relationship between TC grade and clinical symptom severity are lacking.To investigate the clinical characteristics of small-breed dogs diagnosed with TC and determine if fluoroscopic grading correlates with cough severity.We retrospectively reviewed medical records from 2022 to 2024. TC diagnosis was confirmed using fluoroscopic examination. Multiple linear regression was employed to investigate factors influencing cough severity, with a significance level set at p < .05.Results: A total of 132 dogs with TC were identified, of which 22 were excluded. The final cohort consisted of 110 dogs, aged between 2-19 years, with no significant sex differences. The majority (97.2%) of dogs had a BCS of ≥4. Among the top four breeds (Maltese, Pomeranian, Poodle, and Chihuahua), the most severe collapse was observed in the carinal region. The grade of collapse on fluoroscopy was mostly related to high BCS (p <.007) and low body weight (p <.001). However, interestingly, fluoroscopic findings of collapse location and grade did not correlate with cough severity (p = .350). Notably, clinical symptoms improved in 86.6% of cases following interventions such as weight reduction, environmental changes, and pharmacotherapy.In small-breed dogs, the severity of cough was not associated with the region or grade of TC diagnosed by fluoroscopy. However, small body size, along with a high BCS was a key factor in the severity of the collapse.